How can EFL teachers make their questions more interactive with students? Interpersonal patterns of teacher questions - Yang, Xueyan (System (Linköping), 2021)
Teacher questioning is central to effective EFL teaching as it affects student participation in classroom interaction, but a discrepancy is often found between questions considered effective by theorists and those teachers actually ask in practice. Adopting the perspective of Systemic Functional Linguistics, this study addresses teacher questions as ‘interactive events’ whose degrees of interactivity vary with teachers’ choices of interpersonal meanings realized in grammatical forms, with a view to informing EFL teachers how to choose interpersonal meanings to make their questions more interactive with students. Using authentic question-answer sequences (n = 433) occurring in whole-class discussions in 18 college EFL classes in China, the study first analyzed interpersonal choices of ‘Subject person’ (interactant vs. non-interactant) and ‘modal deixis’ (judgment vs. time) in EFL teachers’ questions, and then tested the relationship between teachers’ choices and the length of student answers. Those choices found to be significantly associated with lengthier answers include [interactant + judgment] inviting self-related assessment, [interactant + past] requesting recounts of personal experiences, and [non-interactant + past] seeking reconstruction of textbook discourse. All interpersonal patterns of teacher questions thus identified are described, and pedagogical implications discussed. •A systemic-functional approach to properties of teacher questions.•Teacher questions as interactive events between teachers and students.•Teacher questions as the product of teachers’ choices of interpersonal meanings.•Interpersonal patterns that make teacher questions more interactive with students.•A tool kit for EFL teachers to improve their questioning practices in classrooms.